Effect of Activator Types on the Production of Activated Carbon from Cocoa (Theobroma cacao, L.) Pod Husk as Metal Adsorbent - Aisman Aisman; Sahadi Didi Ismanto; Nadila Aprilianda (Lembaga Penelitian dan Pengabdian, Universitas Andalas, 2023)
The objective of this study is to investigate the distinctive properties of activated carbon derived from cocoa pod husks that have been activated using various activators. The study seeks to assess the absorption capacity of the resulting activated carbon for the heavy metal Fe, and to identify the most effective activator for this purpose. The activators used were ZnCl2, H3PO4, KOH, and MgCl2 each at a concentration of 10%. The characteristics of the activated carbon produced include; yield 70.18–82.24%, water content 0.75–2.25%, ash content 3.50–11.00%, part lost on heating 950? or volatile matter 9.38–15.61 %, pure activated carbon of 76.94–79.16%, and absorption of iodine of 574.36–628.30 mg/g. The utilization of activated carbon derived from cocoa pod husks has demonstrated its efficacy in the adsorption of the heavy metal iron (Fe) present in well water. This adsorption process exhibits a notable absorption capacity within the range of 0.0967–0.0991 mg/g, accompanied by a high absorption efficiency ranging from 96.62% to 99.02%. The most effective activator, as determined by its iodine number, was found to be potassium hydroxide (KOH), which exhibited an impressive absorption capacity of 628.30 mg/g of iodine. On the other hand, magnesium chloride (MgCl2) emerged as the most economically viable activator, with a price of Rp. 30,00 per gram.